Research on implementation factors of product ecological design based on digital collaboration - Qing Liu; Yongzhong Zhang (Sustainable Operations and Computers)
To assist enterprises in adapting to the challenges of the digital era during the product eco-design stage, based on the synergistic symbiosis theory and the eco-strategy wheel, combined with literature research and expert interviews, this study identifies 11 factors for enterprises to realize product eco-design under digital collaboration. In this study, the Decision-making Trial and Evaluation Laboratory (DEMATEL) method was used to aggregate the identified 11 factors into four factor sets: strong cause, weak cause, strong result, and weak result; and the Interpretive Structural Model (ISM) was used to create a multilevel recursive model of product eco-design for digital collaboration. The study's findings show that: digital collaborative product eco-design is a combination of intra-organizational, intra-organizational, and external organizational synergies; and digital collaboration improves the efficiency of eco-design technology acquisition. This research provides a scientific foundation for company managers to make product eco-design decisions in the context of the worldwide digitalization trend.